Gibraltar Identity and Empire. - Archer, E. G. (Routledge advances in European politics., 2013)
The principal argument in Gibraltar and Empire is that Gibraltarians constitute a separate and distinctive people, notwithstanding the political stance taken by the government of Spain. Various factors - environmental, ethnic, economic, political, religious, linguistic, educational and informal - are adduced to explain the emergence of a sense of community on the Rock and an attachment to the United Kingdom. A secondary argument is that the British empire has left its mark in Gibraltar in various forms - such as militarily - and for a number of reasons. Gilbraltar and Em.